Climate change and technology: Examining opinion formation of geoengineering - CUMMINGS, Christopher L. (Institutional Knowledge at Singapore Management University, 2018)
The term “climate change” has evolved from what was originally a technical term employed by scientists into a symbolic referent involving complex social, political, and moral considerations that have spurred worldwide debate. As evidence of the anthropogenic influence on the Earth’s climate has grown over the past few decades, climate change has come to be viewed as a primary challenge to be confronted in the twenty-first century. Geoengineering, or climate engineering, is a set of large-scale technological interventions proposed to offset climatic changes. This study seeks to understand which factors contribute to, or alternatively, detract from public acceptance of geoengineering through robust path analytic modeling of public perceptions of geoengineering that may better serve the academic community and decision-makers. This study finds that familiarity, epistemic trust, preference for alternative solutions to climate change, and media consumption are interrelated in their influences on opinions toward geoengineering proposals and support for funding further geoengineering research. Such predictive modeling can enable risk communicators and policy-makers with vital information to support anticipatory governance approaches to policy initiatives and improve future public engagement and communication about geoengineering.